Predictors of Driving Status in Service Members and Veterans at 1 Year Posttraumatic Brain Injury: A VA TBI Model Systems Study. Issue 6 (5th November 2021) - Bernstein, John P. K.; Sevigny, Mitch; Novack, Thomas A.; Dreer, Laura E.; Chung, Joyce; Lamberty, Greg J.; Finn, Jacob A.
Abstract : Objective: To identify predictors of driving status in service members and veterans 1 year following a traumatic brain injury (TBI). Setting: The 5 Department of Veterans Affairs (VA) Polytrauma Rehabilitation Centers (PRCs). Participants: A total of 471 service members and veterans (128 with mild/complicated mild TBI and 343 with moderate/severe TBI) who received TBI-focused inpatient rehabilitation at one of the VA PRCs and who participated in a 1-year postinjury follow-up assessment. Design: Secondary analysis from the Department of Veterans Affairs Polytrauma Rehabilitation Centers Traumatic Brain Injury Model Systems (VA PRC TBIMS) national database. Main Measures: Primary outcome was a single item that assessed driving status at 1 year postinjury. Predictor variables included demographics; sensory impairment, substance use, and employment status at time of injury; PTSD symptoms reported at study enrollment; and functional impairment rated at rehabilitation discharge. Results: In unadjusted bivariate analyses, among those with a mild/complicated mild TBI, older age and greater functional impairment were associated with lower likelihood of driving. Among those with a moderate/severe TBI, discharge to a nonprivate residence, greater functional impairment, and higher PTSD symptoms were linked to lower likelihood of driving. Adjusted multivariate analyses indicated that functional impairment was uniquely associated with driving status in both TBI severity groups. After controlling for other predictors, self-reported PTSD symptoms, particularly dysphoria symptoms, were associated with lower likelihood of driving in both severity groups. Conclusion: Given the significance of clinician-rated functional impairment and self-reported PTSD symptoms to the prediction of driving status 1 year post-TBI among service members and veterans, rehabilitation efforts to improve functioning and reduce negative affect may have a positive impact on driving and community integration.